CO2 adsorption-catalytic hydrogenation coupling material as well as preparation method and application thereof

By loading the coupling material of CU, CO, and K on the UIO-66 matrix, the problem of complex and cost-high costs of CO2 adsorption and catalytic hydrogenation process in existing technologies, and realized CO2 efficient separation and catalytic hydrogenation conversion, which promoted the promotion Carbon emission reduction and resource use.

CN119368236APending Publication Date: 2025-01-28YANCHENG LANFENG ENVIRONMENTAL ENG TECH +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411420080.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-12
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

When realizing carbon capture and utilization of the prior art, the two processes of CO2 adsorption and catalytic hydrogenation are complex and have high operating costs, which is not conducive to industrial promotion.

Method used

Develop a CO2 adsorption-catalytic hydrogen coupling material, use the heating back-to-reinvable provider UIO-66 by loading CU, CO, and K on the UIO-66 matrix, and absorb dryness through the CUCO dual metal MOFS package and fluidized bed spray spray spray spray. Method K components to achieve high -efficiency separation and catalytic hydrogenation conversion of CO2.

Benefits of technology

The efficient separation and catalytic hydrogenation conversion of CO2 in an integrated process has been achieved at the same time, reducing process complexity and operating costs, and providing new ideas for carbon emission reduction and resource utilization.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119368236A_ABST
    Figure CN119368236A_ABST
Patent Text Reader

Abstract

The invention discloses a CO2 adsorption-catalytic hydrogenation coupling material as well as a preparation method and application thereof, a carrier UiO-66 is prepared by adopting a heating reflux method, Cu, Co and K are loaded on the UiO-66 by adopting a bimetal MOFs (Metal-Organic Frameworks) wrapping calcination method and a fluidized bed spray absorption drying method, and the mass ratio of Cu to Co to K to UiO-66 is (2-6): 2: 20: 100. The coupling material has the following advantages: (1) the coupling material simultaneously has two functions of CO2 adsorption and ethanol preparation through catalytic hydrogenation; (2) the specific surface area is higher; (3) amino alkaline adsorption sites on the surface of the UiO-66 are more, and the dispersion is more uniform; and (4) the dispersibility, CO2 adsorption performance and catalytic hydrogenation performance of the active component are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of carbon dioxide adsorption separation and catalytic conversion, and in particular relates to a CO2 adsorption-catalytic hydrogenation coupling material and a preparation method and application thereof. Background Art

[0002] The CO2 emissions from the combustion of fossil fuels such as coal, oil and natural gas continue to rise, triggering a series of chain reactions such as ozone layer depletion, climate warming, greenhouse effect, sea level rise, ecosystem destruction, food production reduction, severe weather and frequent natural disasters, endangering human life, production and development. In recent years, countries have adopted carbon sink measures such as afforestation and vegetation restoration to absorb carbon dioxide in the atmosphere through photosynthesis, thereby reducing carbon dioxide in the atmosphere. However, it is still unable to completely offset the huge CO2 emissions.

[0003] Carbon capture, utilization and storage (CCUS) is regarded as an effective way to achieve global carbon emission reduction, and it is also of great significance to energy security and coordinated economic development. If CCUS technology can be applied on a large scale in industries such as electricity, steel, cobalt, and cement, it will significantly reduce carbon emissions in these industries, and at the same time, excess carbon emission quotas can be converted into economic benefits through carbon trading. This technology is divided into three processes: capturing and separating CO2 from emission sources, utilizing the separated CO2, and permanently storing the separated CO2. Among various carbon capture technologies, adsorption has the advantages of low energy consumption and simple operation. Among CO2 utilization technologies, catalytic hydrogenation can convert CO2 into high value-added products. Both CO2 adsorption and CO2 catalytic hydrogenation have a broad research basis and have achieved industrial demonstration, but the "two processes + two materials" have complex processes and high operating costs, which is not conducive to their industrial promotion. The core technologies of the two processes are the design of adsorbents and catalysts, respectively. The common point is that the materials are porous materials, and the adsorption and catalytic processes are closely related. Therefore, developing a coupling material that integrates CO2 adsorption and catalytic hydrogenation, and realizing efficient CO2 separation and catalytic hydrogenation conversion in one material and one process, is of great significance to carbon emission reduction and resource utilization. Summary of the invention

[0004] At present, carbon capture and utilization require the two processes of CO2 adsorption and catalytic hydrogenation, which have the disadvantages of complex process and high operating cost, which is not conducive to its industrial promotion. In view of the problem that it is not conducive to its industrial promotion, the development of coupling materials that can achieve efficient CO2 separation and catalytic hydrogenation conversion in one integrated process will provide new ideas for carbon emission reduction and resource utilization.

[0005] In order to solve the problems of the prior art, the technical solution adopted by the present invention is: A CO2 adsorption-catalytic hydrogenation coupling material, which takes UiO-66 as a matrix, and loads Cu, Co and K on UiO-66, and the mass ratio of Cu: Co K: UiO-66 is (2-6): 2: 20: 100.

[0006] A method for preparing a CO2 adsorption-catalytic hydrogenation coupling material comprises the following steps: Step 1, preparing the carrier UiO-66 by heating reflux method, dissolving zirconium chloride, terephthalic acid and amino modifier in a mixed solvent of methanol and water at a mass ratio of 1.4: 1: 1, the volume ratio of methanol to water is 3: 1, and after mixing evenly, transferring to a round-bottom flask connected to a condenser at the upper end, placing the round-bottom flask in an electric heating mantle for heating reaction under condensation reflux, cooling to room temperature after the reaction is completed, pouring out the mother liquor, obtaining a white precipitate, washing the white precipitate with ethanol 3 times, and drying under vacuum conditions to obtain the carrier UiO-66; Step 2: add copper acetate, cobalt chloride, 2-aminoterephthalic acid and UiO-66 prepared in step 1 to a mixed solution of DMF, ethanol and deionized water in a certain proportion, stir and dissolve, transfer to a beaker, react at 80 °C under magnetic stirring for 12 hours, cool to room temperature, wash the product with ethanol and dry it at 80 °C overnight to obtain CuCo bimetallic MOFs-wrapped UiO-66, recorded as Cu x Co2(NH2BDC)@UiO-66, where x=2-6; Step 3, using high pressure hot air flow to heat the Cu x Co2(NH2BDC)@UiO-66 powder is sprayed into the inlet at the lower end of the fluidized bed to keep the powder in a fluidized state, and then potassium carbonate solution is sprayed on the upper end of the fluidized bed. The potassium carbonate solution is fully in contact with the fluidized powder to complete the absorption, loading and drying of potassium carbonate, which is recorded as K 20 / Cu x Co2(NH2BDC)@UiO-66; Step 4: K prepared in step 3 20 / Cu x Co2(NH2BDC)@UiO-66 was heated in a tube furnace for 4 h to obtain a CO2 adsorption-catalytic hydrogenation coupling material, denoted as Cu x Co2K 20 @UiO-66, where x=2-6.

[0007] The amino-modifying agent used in step 1 is ammonium carbonate, which can be decomposed under heating to produce ammonia gas for amino-modification; In step 1, the reflux temperature is 85°C and the reaction time is 48 h, which can make the reaction system in a boiling homogeneous state; In step 2, the mass ratio of copper in copper acetate, cobalt in cobalt chloride, 2-aminoterephthalic acid and UiO-66 is (2-6): 2: 12: 100, and the volume ratio of DMF, ethanol and deionized water is 6: 1: 1.

[0008] In step 2, during the reaction, the mouth of the beaker is covered with a plastic film with dense small holes to exhaust and dissipate heat while minimizing the volatilization loss of the solvent.

[0009] In step 3, the temperature of the high-pressure hot air flow is 80°C, the pressure is 1MPa, and the potassium carbonate and Cu x The mass ratio of Co2(NH2BDC)@UiO-66 powder is 1:5.

[0010] Furthermore, the treatment temperature in the tube furnace in step 4 is 450 °C, which ensures that the Cu x Co2(NH2BDC) can be decomposed into oxides without destroying the structure of UiO-66; the atmosphere during heating in the tubular furnace is a H2 atmosphere, which ensures that the decomposed oxides are reduced to low-valent species with catalytic activity.

[0011] A CO2 adsorption-catalytic hydrogenation coupling material is used for the capture, adsorption and / or catalytic hydrogenation preparation process of CO2.

[0012] Beneficial effects: Compared with the prior art, the CO2 adsorption-catalytic hydrogenation coupling material of the present invention and its preparation method and application have the following advantages: (1) The coupling material has both CO2 adsorption and catalytic hydrogenation to ethanol; (2) The carrier UiO-66 prepared by the heating reflux method has a higher specific surface area; (3) UiO-66 is amino-modified by thermal decomposition of ammonium carbonate to produce ammonia, so that the alkaline adsorption sites on the surface of UiO-66 are more numerous and more evenly dispersed; (4) The Cu and Co components are loaded by calcining UiO-66 wrapped with CuCo bimetallic MOFs, which can make the binding effect between Cu and Co stronger, improve the efficiency of electron transfer between the two and the catalytic hydrogenation performance; (5) The use of fluidized bed spray absorption drying method to load the K component can significantly reduce the influence of component loading on the specific surface area and pore volume, and improve the dispersibility of the active component and the CO2 adsorption performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 SEM images of different samples: (a) UiO-66 prepared in Example 1, (b) D1-UiO-66 prepared in Comparative Example 1, (c) D3-Cu4Co2K prepared in Comparative Example 3 20 @UiO-66, (d) Cu4Co2K prepared in Example 3 20 @UiO-66; Figure 2 The graphs are the test results of specific surface area and pore structure of different samples; Figure 3 CO2 adsorption of different samples: (a) UiO-66 prepared in Example 1, (b) D1-UiO-66 prepared in Comparative Example 1, (c) Cu2Co2K prepared in Example 2 20 @UiO-66, (d) Cu4Co2K prepared in Example 3 20 @UiO-66, (e) Cu6Co2K prepared in Example 4 20 @UiO-66, (f) D2-Cu2Co2K prepared in Comparative Example 2 20 @UiO-66, (g) D3-Cu4Co2K prepared in Comparative Example 3 20 @UiO-66, (h) D4-Cu6Co2K prepared in Comparative Example 4 20 @UiO-66; Figure 4 The pH value results of different samples before and after CO2 adsorption when the zeta potential is zero; Figure 5 The ethanol selectivity of CO2 hydrogenation reaction of different samples: (a) UiO-66 prepared in Example 1, (b) D1-UiO-66 prepared in Comparative Example 1, (c) Cu2Co2K prepared in Example 2 20 @UiO-66, (d) Cu4Co2K prepared in Example 3 20 @UiO-66, (e) Cu6Co2K prepared in Example 4 20 @UiO-66, (f) D2-Cu2Co2K prepared in Comparative Example 2 20 @UiO-66, (g) D3-Cu4Co2K prepared in Comparative Example 3 20 @UiO-66, (h) D4-Cu6Co2K prepared in Comparative Example 4 20 @UiO-66; Figure 6 CO2 conversion rate and ethanol yield of hydrogenation reaction of different samples: (a) UiO-66 prepared in Example 1, (b) D1-UiO-66 prepared in Comparative Example 1, (c) Cu2Co2K prepared in Example 2 20 @UiO-66, (d) Cu4Co2K prepared in Example 3 20 @UiO-66, (e) Cu6Co2K prepared in Example 4 20 @UiO-66, (f) D2-Cu2Co2K prepared in Comparative Example 2 20@UiO-66, (g) D3-Cu4Co2K prepared in Comparative Example 3 20 @UiO-66, (h) D4-Cu6Co2K prepared in Comparative Example 4 20 @UiO-66. DETAILED DESCRIPTION

[0014] The present invention will be further described below in conjunction with specific embodiments and comparative examples. According to the following examples, the present invention can be better understood. However, it is easy for those skilled in the art to understand that the specific material proportions, process conditions and results described in the embodiments are only used to illustrate the present invention, and should not and will not limit the present invention described in detail in the claims.

[0015] Example 1

[0016] The carrier UiO-66 was prepared by a heating reflux method. Zirconium chloride, terephthalic acid and amino modifier were dissolved in 140 mL of a mixed solvent of methanol and water with a volume ratio of 3:1 at a mass ratio of 1.4:1:1. After being mixed evenly, the mixture was transferred to a 250 mL round-bottom flask with a condenser connected to the upper end. The round-bottom flask was placed in an electric heating mantle under condensation reflux and reacted at 85 °C for 48 h. After the reaction was completed, the mixture was cooled to room temperature, and the mother liquor was poured out to obtain a white precipitate. The white precipitate was washed three times with ethanol and dried under vacuum conditions to obtain the carrier UiO-66.

[0017] Example 2

[0018] (1) The carrier UiO-66 was prepared by the heating reflux method. Zirconium chloride, terephthalic acid and amino-modifying agent ammonium carbonate were dissolved in a mixed solvent of 140 mL methanol and water (volume ratio 3:1) at a ratio of 1.4: 1: 1 (mass ratio). After being mixed evenly, the mixture was transferred to a 250 mL round-bottom flask with a condenser connected to the upper end. The round-bottom flask was placed in an electric heating mantle and heated to 85 °C under condensation reflux. The system was kept in a boiling homogeneous state and reacted for 48 h. Ammonium carbonate was decomposed under heating to produce ammonia for amino modification. After the reaction was completed, the mixture was cooled to room temperature and the mother liquor was poured out to obtain a white precipitate. The white precipitate was washed three times with ethanol and dried under vacuum to obtain the carrier UiO-66. (2) Copper acetate, cobalt chloride, 2-aminoterephthalic acid and UiO-66 were added to a mixed solution of 120 mL DMF, ethanol and deionized water (volume ratio of 6: 1: 1) in a mass ratio of copper: cobalt: 2-aminoterephthalic acid: UiO-66 = 2: 2: 12: 100, stirred and dissolved, and then transferred to a 200 mL beaker. The mouth of the beaker was covered with a layer of plastic film with dense small holes to minimize the volatile loss of the solvent while venting and dissipating the heat. The reaction was carried out at 80 °C under magnetic stirring for 12 hours. After cooling to room temperature, the product was washed with ethanol and dried at 80 °C overnight to obtain CuCo bimetallic MOFs-encapsulated UiO-66, recorded as Cu2Co2(NH2BDC)@UiO-66; (3) The Cu2Co2(NH2BDC)@UiO-66 powder was sprayed into the lower entrance of the fluidized bed using a high-pressure hot air flow at 80 °C and 1 MPa to keep the powder in a fluidized state. Then, potassium carbonate solution was sprayed on the upper end of the fluidized bed. The mass ratio of potassium carbonate to powder was 1:5. The potassium carbonate solution was in full contact with the fluidized powder to complete the absorption, loading and drying of potassium carbonate, which was recorded as K 20 / Cu2Co2(NH2BDC)@UiO-66.

[0019] (4) K 20 / Cu2Co2(NH2BDC)@UiO-66 was placed in a tube furnace and heated at 450 ℃ in H2 atmosphere for 4 h to ensure that Cu x Co2(NH2BDC) can be decomposed into oxides without destroying the structure of UiO-66 to obtain CO2 adsorption-catalytic hydrogenation coupling material, recorded as Cu2Co2K 20 @UiO-66.

[0020] Example 3

[0021] (1) The carrier UiO-66 was prepared by the heating reflux method. Zirconium chloride, terephthalic acid and amino-modifying agent ammonium carbonate were dissolved in a mixed solvent of 140 mL methanol and water (volume ratio 3:1) at a ratio of 1.4: 1: 1 (mass ratio). After being mixed evenly, the mixture was transferred to a 250 mL round-bottom flask with a condenser connected to the upper end. The round-bottom flask was placed in an electric heating mantle and heated to 85 °C under condensation reflux. The system was kept in a boiling homogeneous state and reacted for 48 h. Ammonium carbonate was decomposed under heating to produce ammonia for amino modification. After the reaction was completed, the mixture was cooled to room temperature and the mother liquor was poured out to obtain a white precipitate. The white precipitate was washed three times with ethanol and dried under vacuum to obtain the carrier UiO-66. (2) Copper acetate, cobalt chloride, 2-aminoterephthalic acid and UiO-66 were added to a mixed solution of 120 mL DMF, ethanol and deionized water (volume ratio of 6: 1: 1) in a mass ratio of copper: cobalt: 2-aminoterephthalic acid: UiO-66 = 4: 2: 12: 100, stirred and dissolved, and then transferred to a 200 mL beaker. The beaker mouth was covered with a layer of plastic film with dense small holes to minimize the solvent volatilization loss while exhausting the heat. The reaction was carried out at 80 ° C and magnetic stirring for 12 hours. After cooling to room temperature, the product was washed with ethanol and dried at 80 ° C overnight to obtain CuCo bimetallic MOFs-encapsulated UiO-66, recorded as Cu4Co2(NH2BDC)@UiO-66; (3) The Cu2Co2(NH2BDC)@UiO-66 powder was sprayed into the lower entrance of the fluidized bed using a high-pressure hot air flow at 80 °C and 1 MPa to keep the powder in a fluidized state. Then, potassium carbonate solution was sprayed on the upper end of the fluidized bed. The mass ratio of potassium carbonate to powder was 1:5. The potassium carbonate solution was in full contact with the fluidized powder to complete the absorption, loading and drying of potassium carbonate, which was recorded as K 20 / Cu4Co2(NH2BDC)@UiO-66.

[0022] (4) K 20 / Cu4Co2(NH2BDC)@UiO-66 was placed in a tube furnace and heated at 450 ℃ in H2 atmosphere for 4 h to ensure that Cu x Co2(NH2BDC) can be decomposed into oxides without destroying the structure of UiO-66 to obtain CO2 adsorption-catalytic hydrogenation coupling material, recorded as Cu4Co2K 20 @UiO-66.

[0023] Example 4

[0024] (1) The carrier UiO-66 was prepared by the heating reflux method. Zirconium chloride, terephthalic acid and amino-modifying agent ammonium carbonate were dissolved in a mixed solvent of 140 mL methanol and water (volume ratio 3:1) at a ratio of 1.4: 1: 1 (mass ratio). After being mixed evenly, the mixture was transferred to a 250 mL round-bottom flask with a condenser connected to the upper end. The round-bottom flask was placed in an electric heating mantle and heated to 85 °C under condensation reflux. The system was kept in a boiling homogeneous state and reacted for 48 h. Ammonium carbonate was decomposed under heating to produce ammonia for amino modification. After the reaction was completed, the mixture was cooled to room temperature and the mother liquor was poured out to obtain a white precipitate. The white precipitate was washed three times with ethanol and dried under vacuum to obtain the carrier UiO-66. (2) Copper acetate, cobalt chloride, 2-aminoterephthalic acid and UiO-66 were added to a mixed solution of 120 mL DMF, ethanol and deionized water (volume ratio of 6: 1: 1) in a mass ratio of copper: cobalt: 2-aminoterephthalic acid: UiO-66 = 6: 2: 12: 100, stirred and dissolved, and then transferred to a 200 mL beaker. The beaker mouth was covered with a layer of plastic film with dense small holes to minimize the solvent volatilization loss while exhausting the heat. The reaction was carried out at 80 ° C with magnetic stirring for 12 hours. After cooling to room temperature, the product was washed with ethanol and dried at 80 ° C overnight to obtain CuCo bimetallic MOFs-encapsulated UiO-66, recorded as Cu6Co2(NH2BDC)@UiO-66; (3) The Cu2Co2(NH2BDC)@UiO-66 powder was sprayed into the lower entrance of the fluidized bed using a high-pressure hot air flow at 80 °C and 1 MPa to keep the powder in a fluidized state. Then, potassium carbonate solution was sprayed on the upper end of the fluidized bed. The mass ratio of potassium carbonate to powder was 1:5. The potassium carbonate solution was in full contact with the fluidized powder to complete the absorption, loading and drying of potassium carbonate, which was recorded as K 20 / Cu6Co2(NH2BDC)@UiO-66.

[0025] (4) K 20 / Cu6Co2(NH2BDC)@UiO-66 was placed in a tube furnace and heated at 450 ℃ in H2 atmosphere for 4 h to ensure that Cu x Co2(NH2BDC) can be decomposed into oxides without destroying the structure of UiO-66 to obtain CO2 adsorption-catalytic hydrogenation coupling material, recorded as CuCo2K 20 @UiO-66.

[0026] Comparative Example 1

[0027] The carrier UiO-66 was prepared by a solvothermal method. Zirconium chloride, terephthalic acid and ammonia water were dissolved in a mixed solvent of 140 mL methanol and water (volume ratio 3:1) at a ratio of 1.4: 1: 1 (mass ratio). After mixing evenly, the mixture was transferred to a polytetrafluoroethylene-lined reactor and reacted at 150 °C for 24 h. After the reaction was completed, the mixture was cooled to room temperature and the mother liquor was poured out to obtain a white precipitate. The white precipitate was washed three times with ethanol and dried under vacuum conditions to obtain the carrier D1-UiO-66.

[0028] Comparative Example 2

[0029] (1) The carrier UiO-66 was prepared by the heating reflux method. Zirconium chloride, terephthalic acid and amino-modifying agent ammonium carbonate were dissolved in a mixed solvent of 140 mL methanol and water (volume ratio 3:1) at a ratio of 1.4: 1: 1 (mass ratio). After being mixed evenly, the mixture was transferred to a 250 mL round-bottom flask with a condenser connected to the upper end. The round-bottom flask was placed in an electric heating mantle and heated to 85 °C under condensation reflux. The system was kept in a boiling homogeneous state and reacted for 48 h. Ammonium carbonate was decomposed under heating to produce ammonia for amino modification. After the reaction was completed, the mixture was cooled to room temperature and the mother liquor was poured out to obtain a white precipitate. The white precipitate was washed three times with ethanol and dried under vacuum to obtain the carrier UiO-66. (2) Copper acetate, cobalt chloride, potassium carbonate and UiO-66 were added to 120 mL of deionized water in a mass ratio of copper: cobalt: potassium carbonate: UiO-66 = 2: 2: 20: 100, and the mixture was immersed in water under magnetic stirring for 12 hours. The product was then washed with ethanol and dried at 80 °C overnight to obtain UiO-66 impregnated with copper acetate, cobalt chloride and potassium carbonate, denoted as K 20 / Cu2Co2(SALT)@UiO-66; (3) K 20 / Cu2Co2(SALT)@UiO-66 was placed in a tube furnace and heated at 450 °C in a H2 atmosphere for 4 h to ensure that the metal salt could be decomposed into oxides without destroying the structure of UiO-66, thus obtaining a CO2 adsorption-catalytic hydrogenation coupling material, denoted as D2-Cu2Co J2 K 20 @UiO-66.

[0030] Comparative Example 3

[0031] (1) The carrier UiO-66 was prepared by the heating reflux method. Zirconium chloride, terephthalic acid and amino-modifying agent ammonium carbonate were dissolved in a mixed solvent of 140 mL methanol and water (volume ratio 3:1) at a ratio of 1.4: 1: 1 (mass ratio). After being mixed evenly, the mixture was transferred to a 250 mL round-bottom flask with a condenser connected to the upper end. The round-bottom flask was placed in an electric heating mantle and heated to 85 °C under condensation reflux. The system was kept in a boiling homogeneous state and reacted for 48 h. Ammonium carbonate was decomposed under heating to produce ammonia for amino modification. After the reaction was completed, the mixture was cooled to room temperature and the mother liquor was poured out to obtain a white precipitate. The white precipitate was washed three times with ethanol and dried under vacuum to obtain the carrier UiO-66. (2) Copper acetate, cobalt chloride, potassium carbonate and UiO-66 were added to 120 mL of deionized water in a mass ratio of copper: cobalt: potassium carbonate: UiO-66 = 4: 2: 20: 100, and the mixture was immersed in water for 12 hours under magnetic stirring. The product was then washed with ethanol and dried at 80 °C overnight to obtain UiO-66 impregnated with copper acetate, cobalt chloride and potassium carbonate, denoted as K 20 / Cu4Co2(SALT)@UiO-66; (3) K 20 / Cu4Co2(SALT)@UiO-66 was placed in a tube furnace and heated at 450 °C in a H2 atmosphere for 4 h, which ensured that the metal salt could be decomposed into oxides without destroying the structure of UiO-66, and a CO2 adsorption-catalytic hydrogenation coupling material was obtained, which was recorded as D3-Cu4Co2K 20 @UiO-66.

[0032] Comparative Example 4

[0033] (1) The carrier UiO-66 was prepared by the heating reflux method. Zirconium chloride, terephthalic acid and amino-modifying agent ammonium carbonate were dissolved in a mixed solvent of 140 mL methanol and water (volume ratio 3:1) at a ratio of 1.4: 1: 1 (mass ratio). After being mixed evenly, the mixture was transferred to a 250 mL round-bottom flask with a condenser connected to the upper end. The round-bottom flask was placed in an electric heating mantle and heated to 85 °C under condensation reflux. The system was kept in a boiling homogeneous state and reacted for 48 h. Ammonium carbonate was decomposed under heating to produce ammonia for amino modification. After the reaction was completed, the mixture was cooled to room temperature and the mother liquor was poured out to obtain a white precipitate. The white precipitate was washed three times with ethanol and dried under vacuum to obtain the carrier UiO-66. (2) Copper acetate, cobalt chloride, potassium carbonate and UiO-66 were added to 120 mL of deionized water in a mass ratio of copper: cobalt: potassium carbonate: UiO-66 = 6: 2: 20: 100, and the mixture was immersed in water under magnetic stirring for 12 hours. The product was then washed with ethanol and dried at 80 °C overnight to obtain UiO-66 impregnated with copper acetate, cobalt chloride and potassium carbonate, denoted as K 20 / Cu6Co2(SALT)@UiO-66; (3) K 20 / Cu6Co2(SALT)@UiO-66 was placed in a tube furnace and heated at 450 °C in a H2 atmosphere for 4 h, which ensured that the metal salt could be decomposed into oxides without destroying the structure of UiO-66, and a CO2 adsorption-catalytic hydrogenation coupling material was obtained, which was recorded as D4-Cu6Co2K 20 @UiO-66.

[0034] Scanning electron microscopy (SEM) was used to characterize the morphology of the samples, and a zeta potential meter was used to measure the pH value (pH pzc ), the CO2 adsorption performance of the material was tested by thermogravimetric analyzer; the CO2 catalytic hydrogenation to ethanol performance test of the above coupling material was carried out on a fixed bed reactor (stainless steel reaction tube inner diameter 10mm), the catalyst loading was 0.5g, and it was mixed with 0.5g quartz sand. The reduction temperature was slightly higher than the reaction temperature. When the reaction temperature was cooled to 220℃, a mixed gas with a volume ratio of H2:CO2 = 3:1 was introduced, and the reaction pressure was 3.5MPa. The product after the reaction was analyzed by gas chromatography, and then the CO2 conversion rate and ethanol selectivity of the coupling material in the CO2 catalytic hydrogenation to ethanol reaction at 220℃ were obtained.

[0035] Depend on Figure 1 As shown in (a), UiO-66 has an octahedral morphology and a size of about 10 μm. The octahedral surface is smooth and has a small amount of particles attached. Figure 1 (b) is D1-UiO-66, which basically retains the octahedral morphology and size; Figure 1 (c) It can be seen that the D3-Cu4Co2K prepared in Comparative Example 3 20 The number of particles attached to the octahedral surface of @UiO-66 increased, and the particle distribution was uneven. In contrast, the Cu4Co2K 20 @UiO-66 There are many particles attached to the octahedron surface, and the particles are evenly distributed (see Figure 1 (d)). The small particles on the surface may be caused by potassium carbonate loading.

[0036] like Figure 2 As shown in the figure, the specific surface area and pore volume of UiO-66 prepared in Example 1 are 1184 m 2 / g and 0.86m 3 / g, the specific surface area and pore volume of D1-UiO-66 prepared in Comparative Example 1 decreased to 852 m 2 / g and 0.79m 3 / g. Compared with the solvothermal method, the UiO-66 prepared by the reflux method has a higher specific surface area and pore volume. The specific surface area and pore volume of the samples of Examples 2-4 range from 889 to 937 m 2 / g and 0.71-0.74m 3 / g, while the specific surface area and pore volume of samples in Comparative Examples 2-4 range from 665 to 751 m 2 / g and 0.51-0.58m 3 / g, which shows that the use of impregnation method to load components such as Cu, Co and K onto UiO-66 will lead to a significant decrease in specific surface area and pore volume, while the calcination method of UiO-66 wrapped with CuCo bimetallic MOFs to load Cu and Co components, and the fluidized bed spray absorption drying method to load K component will significantly improve the effect of the three-component loading on the specific surface area and pore volume.

[0037] like Figure 3 As shown, the CO2 adsorption capacity of UiO-66 prepared in Example 1 and D1-UiO-66 prepared in Comparative Example 1 at 220°C is 0.71 mmol / g and 0.66 mmol / , respectively, which is consistent with the law of specific surface area, indicating that the adsorption of CO2 by both is mainly physical adsorption. The CO2 adsorption capacity of the samples of Examples 2-4 increases with the increase of Cu and Co doping amounts, and the CO2 adsorption capacity of the three samples is 3.74 mmol / g, 4.08 mmol / g and 4.36 mmol / g, respectively. The CO2 adsorption capacity of the samples of Comparative Examples 2-4 also increases with the increase of Cu and Co doping amounts, and the CO2 adsorption capacity of the three samples is 3.18 mmol / g, 3.37 mmol / g and 3.49 mmol / g, respectively. It can be seen that the calcination method of UiO-66 wrapped with CuCo bimetallic MOFs to load Cu and Co components, and the fluidized bed spray absorption drying method to load K components will significantly improve the CO2 adsorption performance of the sample.

[0038] The pH value (pH) when the zeta potential of the sample is zero before and after CO2 adsorption pzc )like Figure 4 As shown, before CO2 adsorption, the pH of UiO-66 prepared in Example 1 and D1-UiO-66 prepared in Comparative Example 1 pzc The pH values ​​of the samples prepared in Example 2-4 and Comparative Example 2-4 are 8.7 and 8.1, respectively, indicating that the surface alkalinity of UiO-66 prepared in Example 1 is stronger and more conducive to CO2 adsorption. pzc The former is significantly higher than the latter, indicating that the alkaline components such as Cu, Co and K are more evenly dispersed in the former. pzc Both have decreased, but still show weak alkalinity.

[0039] The ethanol selectivity of different samples in the CO2 hydrogenation reaction at 220℃ is shown in Figure 2. Figure 5As shown, the ethanol selectivity of UiO-66 prepared in Example 1 and D1-UiO-66 prepared in Comparative Example 1 are 7.2% and 4.6%, respectively. After using UiO-66 prepared in Example 1 as a carrier to load Cu, Co and K components by different methods, the ethanol selectivities of the samples prepared in Examples 2-4 are 61.7%, 74.2% and 66.8%, respectively, while the ethanol selectivities of the samples in Comparative Examples 2-4 are 60.2%, 72.5% and 65.2%, respectively. The ethanol selectivities of the two samples with the same Cu loading are not much different.

[0040] The CO2 conversion and ethanol yield of different samples at 220℃ are shown in Figure 2. Figure 6 As shown, the CO2 conversion rates of UiO-66 obtained in Example 1 and D1-UiO-66 obtained in Comparative Example 1 are 4.1% and 3.9%, respectively, which are not much different; the ethanol yields are 0.30% and 0.18%, respectively, which are quite different, which is caused by the large difference in the ethanol selectivity of the two. After using UiO-66 obtained in Example 1 as a carrier and loading Cu, Co and K components by different methods, the CO2 conversion rates of the samples obtained in Examples 2-4 are 19.5%, 26.7% and 21.4%, respectively, while the CO2 conversion rates of the samples obtained in Comparative Examples 2-4 are 15.8%, 18.9% and 16.4%, respectively, the former is significantly higher than the latter. The ethanol yields of the samples obtained in Examples 2-4 are 12.03%, 19.81% and 14.30%, respectively, while the CO2 conversion rates of the samples obtained in Comparative Examples 2-4 are 9.51%, 13.70% and 10.69%, respectively, the former is significantly higher than the latter. In summary, the calcination method of UiO-66 wrapped with CuCo bimetallic MOFs to load Cu and Co components, and the fluidized bed spray absorption drying method to load K component will significantly improve the CO2 adsorption performance and catalytic hydrogenation performance of the sample.

Claims

1. A CO2 adsorption-catalytic hydrogenation coupling material, characterized in that: It takes UiO-66 as the matrix, and loads Cu, Co and K on UiO-66, and the mass ratio of Cu: Co: K: UiO-66 is (2-6): 2: 20:

100.

2. A method for preparing the CO2 adsorption-catalytic hydrogenation coupling material according to claim 1, characterized in that: The following steps are involved: Step 1, preparing the carrier UiO-66 by heating reflux method, dissolving zirconium chloride, terephthalic acid and amino modifier in a mixed solvent of methanol and water in a mass ratio of 1.4: 1: 1, mixing evenly and transferring to a round-bottom flask with a condenser connected to the upper end, placing the round-bottom flask in an electric heating mantle for heating reaction under condensation reflux, cooling to room temperature after the reaction, pouring out the mother liquor to obtain a white precipitate, washing the white precipitate with ethanol 3 times, and drying under vacuum conditions to obtain the carrier UiO-66; Step 2: add copper acetate, cobalt chloride, 2-aminoterephthalic acid and UiO-66 prepared in step 1 to a mixed solution of DMF, ethanol and deionized water in a certain proportion, stir and dissolve, transfer to a beaker, react at 80 °C under magnetic stirring for 12 hours, cool to room temperature, wash the product with ethanol and dry it at 80 °C overnight to obtain CuCo bimetallic MOFs-wrapped UiO-66, recorded as Cu x Co2(NH2BDC)@UiO-66, where x=2-6; Step 3, using high pressure hot air flow to heat the Cu x Co2(NH2BDC)@UiO-66 powder is sprayed into the inlet at the lower end of the fluidized bed to keep the powder in a fluidized state, and then potassium carbonate solution is sprayed on the upper end of the fluidized bed. The potassium carbonate solution is fully in contact with the fluidized powder to complete the absorption, loading and drying of potassium carbonate, which is recorded as K 20 / Cu x Co2(NH2BDC)@UiO-66; Step 4: K prepared in step 3 20 / Cu x Co2(NH2BDC)@UiO-66 was heated in a tube furnace for 4 h to obtain a CO2 adsorption-catalytic hydrogenation coupling material, denoted as Cu x Co2K 20 @UiO-66, where x=2-6.

3. The method for preparing the CO2 adsorption-catalytic hydrogenation coupling material according to claim 2, characterized in that: The amino modifier used in step 1 is ammonium carbonate.

4. The method for preparing the CO2 adsorption-catalytic hydrogenation coupling material according to claim 2, characterized in that: The heating reflux temperature in step 1 is 85°C and the reaction time is 48 h.

5. The method for preparing the CO2 adsorption-catalytic hydrogenation coupling material according to claim 2, characterized in that: In step 2, the mass ratio of copper in copper acetate, cobalt in cobalt chloride, 2-aminoterephthalic acid and UiO-66 is (2-6): 2: 12: 100, and the volume ratio of DMF, ethanol and deionized water is 6: 1:

1.

6. The method for preparing the CO2 adsorption-catalytic hydrogenation coupling material according to claim 2, characterized in that: In step 2, during the reaction, the mouth of the beaker is covered with a plastic film with dense small holes.

7. The method for preparing the CO2 adsorption-catalytic hydrogenation coupling material according to claim 2, characterized in that: In step 3, the temperature of the high-pressure hot air flow is 80°C, the pressure is 1MPa, and the potassium carbonate and Cu x The mass ratio of Co2(NH2BDC)@UiO-66 powder is 1:

5.

8. The method for preparing the CO2 adsorption-catalytic hydrogenation coupling material according to claim 2, characterized in that: The treatment temperature in the tube furnace in step 4 is 450° C., and the atmosphere during heating in the tube furnace is a H 2 atmosphere.

9. An application of the CO2 adsorption-catalytic hydrogenation coupling material as claimed in claim 1 for CO2 capture, adsorption and / or catalytic hydrogenation preparation process.